HUBUNGAN SCHOOL WELL-BEING DENGAN PRILAKU AGRESIFITAS SISWA DI SMA KOTA PADANG DAN IMPLIKASINYA TERHADAP BIMBINGAN DAN KONSELING - Asmuliadi, Asmuliadi; Karneli, Yeni (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2018)
Adolescent behavior is influenced by the environment namely the educational environment and peers. School is a context that is important for moral development. School well-being is important to know because it can be used as an evaluation tool for students' welfare in life at school. Students who are not prosperous towards their school can influence students to behave aggressively, namely the desire to intentionally attack or hurt others. This research is to examine the relationship between school well-being and aggressiveness in high school students in Padang City. This study uses cluster random sampling, for class XI students accredited A Private and State High School. Data collection uses two questionnaires namely Questionnaire School well-being (28 items) and the Questionnaire for Aggressiveness (26 items). The results of the analysis using simple regression analysis show a negative correlation between school well-being and aggressiveness (rxy = -0.2). The higher the school well-being, the lower the aggressiveness, and vice versa.Kata kunci: school well-being, aggressiveness.